Cardiovascular events in delayed presentation of HIV: the prospective PISCIS cohort study - Martín-Iguacel, Raquel; Vazquez-Friol, Mari Carmen; Burgos, Joaquin; Bruguera, Andreu; Reyes-Urueña, Juliana; Moreno-Fornés, Sergio; Aceitón, Jordi; Díaz, Yesika; Domingo, Pere; Saumoy, Maria; Knobel, Hernando; Dalmau, David; et al. (Frontiers in Medicine, 2023)
Objectives People with HIV (PWH) have a higher cardiovascular risk than the general population. It remains unclear, however, whether the risk of cardiovascular disease (CVD) is higher in late HIV presenters (LP; CD4 ≤ 350 cells/μL at HIV diagnosis) compared to PWH diagnosed early. We aimed to assess the rates of incident cardiovascular events (CVEs) following ART initiation among LP compared to non-LP. Methods From the prospective, multicentre PISCIS cohort, we included all adult people with HIV (PWH) initiating antiretroviral therapy (ART) between 2005 and 2019 without prior CVE. Additional data were extracted from public health registries. The primary outcome was the incidence of first CVE (ischemic heart disease, congestive heart failure, cerebrovascular, or peripheral vascular disease). The secondary outcome was all-cause mortality after the first CVE. We used Poisson regression. Results We included 3,317 PWH [26 589.1 person/years (PY)]: 1761 LP and 1556 non-LP. Overall, 163 (4.9%) experienced a CVE [IR 6.1/1000PY (95%CI: 5.3–7.1)]: 105 (6.0%) LP vs. 58 (3.7%) non-LP. No differences were observed in the multivariate analysis adjusting for age, transmission mode, comorbidities, and calendar time, regardless of CD4 at ART initiation [aIRR 0.92 (0.62–1.36) and 0.84 (0.56–1.26) in LP with CD4 count <200 and 200– ≤ 350 cells/μL, respectively, compared to non-LP]. Overall mortality was 8.5% in LP versus 2.3% in non-LP (p < 0.001). Mortality after the CVE was 31/163 (19.0%), with no differences between groups [aMRR 1.24 (0.45–3.44)]. Women vs. MSM and individuals with chronic lung and liver disease experienced particularly high mortality after the CVE [aMRR 5.89 (1.35–25.60), 5.06 (1.61–15.91), and 3.49 (1.08–11.26), respectively]. Sensitivity analyses including only PWH surviving the first 2 years yielded similar results. Conclusion CVD remains a common cause of morbidity and mortality among PWH. LP without prior CVD did not exhibit an increased long-term risk of CVE compared with non-LP. Identifying traditional cardiovascular risk factors is essential for CVD risk reduction in this population.